Isolation and Structural Identification of Herbicidal Active Substance from Root of Flaveria bident (L.) Kuntze - Jing-qian HUO; Ji-hong XING; Li-hui ZHANG; Zhan-hai KANG; Jin-lin ZHANG (Journal of Integrative Agriculture)
In order to understand the composition and structure of herbicidal active substance from the root of Flaveria bidentis (L.) Kuntze, the isolation and structural identification were researched in this paper. The crude extract from the root of F. bidentis (L.) Kuntze was extracted by petroleum ether, ethyl acetate, and water saturation of n-butyl alcohol, respectively, and the extraction fluid was separated by using the method of TLC, then the main fraction was separated by HPLC, and the structure of the herbicidal active substance was analyzed by LC-MS, elemental analysis and 1H-NMR. The results showed that the petroleum extraction had the strongest herbicidal activity, and the purple blue stripe separated by TLC had the strongest effect on Digitaria sanguinalis. The herbicidal active substance was identified as α-terthienyl according to the data of LC-MS, elemental analysis and 1H-NMR.